IMPROVEMENT REFRACTORY QUALITY OF ALUMINA SILICATE FOR BRASS SMELTING WITH INFILTRATION TECHNIQUE - Ferli S. Irwansyah; Juliandri Juliandri; Iwan Hastiawan; Soewanto Rahardjo; Rifki Septawendar (Institut Teknologi Bandung, 2010)
Requirement of refractory materials for manufacturing industry and metal smelting is increasing along technology development. Brass smelting needs a larger size ceramic crucible which is known by the name